Foundations of intelligent systems : 23rd International Symposium, ISMIS 2017, Warsaw, Poland, June 26-29, 2017, Proceedings /: 23rd International Symposium, ISMIS 2017, Warsaw, Poland, June 26-29, 2017, Proceedings. (2017) - Unknown
No abstract available